Evolving leadership for collective wellbeing : lessons for implementing the United Nations sustainable development goals - Steffen, Seana Lowe; Rezmovits, Jamie; Trevenna, Shanah; Rappaport, Shana (Building leadership bridges., 2018)
History was made when the United Nations published Transforming Our World: The 2030 Agenda for Sustainable Development and world leaders stepped up to pledge unifying commitments to secure a sustainable future "where all life can thrive." Now, we the peoplethe world's individuals, organizations, and communities that have been championing the shared vision of a sustainable futureneed access to the best leadership guidance available to build on the successes of past efforts and advance breakthrough progress. Evolving Leadership for Collective Wellbeing: Lessons for Implementing the United Nations Sustainable Development Goals provides that guidance. This collection is a go-to resource for individuals wishing to heighten leadership effectiveness through access to vanguard theory and practice. It highlights stories and insights from leadership practitioners and scholars around the world, in the process offering invaluable insights into diverse lessons, models, and practices, and it offers case and place-based chapters that bridge theory and practice to empower diverse actors around the world.As the Agenda acknowledges, "The future of humanity and of our planet lies in our hands. ... It will be for all of us to ensure that the journey is successful and its gains irreversible." Evolving Leadership for Collective Wellbeing is essential reading not only for leaders and leadership scholars, but also for anyone eager to face the Agenda's challenge head on.